Effective stunting prevention: Empowering maternal nutrition education in rural Indonesia through AKUR PENTING intervention - Yuliantie, Putri; Ningrum, Novalia Widiya; Istiqamah (Ananda - Health & Education Foundation, 2024)
Background: Stunting remains a significant public health issue in Indonesia, particularly in rural regions such as Bangun Harjo Village, Central Kalimantan. Stunting affects not only physical growth but also cognitive development, leading to long-term impacts on productivity, health, and quality of life. Despite various government interventions, stunting continues to prevail due to poor maternal nutrition knowledge, inadequate feeding practices, and socio-economic challenges. Case presentation: In Bangun Harjo Village, high stunting rates among toddlers are largely attributed to improper complementary feeding (MPASI) and limited maternal understanding of nutrition. The Kupang Island Health Center initiated a community service intervention called